2019
DOI: 10.23887/mi.v24i2.21262
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Media Video Pembelajaran Dengan Model Pengembangan 4d Pada Mata Pelajaran Agama Hindu

Abstract: AbstrakSeiring perkembangan teknologi yang sangat cepat menyebabkan nilai-nilai agama kurang di perhatikan, sehingga dalam pembelajaran siswa hanya mengetahui namun tidak memahami, padahal ilmu agama merupakan ilmu yang di gunakan sebagai pedoman hidup. Pemahaman siswa terhadap ilmu agama di sebabkan oleh proses pembelajaran yang masih menggunakan metode pembelajaran konvensional tanpa memberikan contoh-contoh konkret dalam proses pembelajaran, sehingga menyebabkan kurangnya pemahaman siswa dan tidak tecapainy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
67

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(168 citation statements)
references
References 0 publications
4
41
0
67
Order By: Relevance
“…Thus, the message conveyed is easy to remember because it is presented attractively and supported by images, text, and audio. Other advantages are able to develop students' opinions and thoughts, it can expand the imagination of students, and many more (Novita et al, 2019;Tegeh, Simamora, & Dwipayana, 2019). Thus, it can be concluded that the use of video media in learning can motivate students' interest and improve the quality of learning, especially students at the primary school level (Kurniawan, Agung, & Tegeh, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the message conveyed is easy to remember because it is presented attractively and supported by images, text, and audio. Other advantages are able to develop students' opinions and thoughts, it can expand the imagination of students, and many more (Novita et al, 2019;Tegeh, Simamora, & Dwipayana, 2019). Thus, it can be concluded that the use of video media in learning can motivate students' interest and improve the quality of learning, especially students at the primary school level (Kurniawan, Agung, & Tegeh, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Video learning has unique features that make it an effective learning method that can enhance and partly replace traditional teacher-led and classroom-based learning approaches. Research conducted by (Purwanti, 2015;Tegeh, Simamora, & Dwipayana, 2019) also stated that videos can help students by visualizing how something works, showing detailed information, attracting students' attention, thereby leading to better learning outcomes. Research conducted by (Aditya, 2017) also stated that the use of audio-visual learning media can motivate students in learning so that it can improve student learning outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the instructional video media could make the students learn independently. Instructional video media can have advantages over other media, namely being able to explain real situations, being able to enrich the explanation when integrated with other media such as text or images, users can repeat certain parts to see a more focused picture, very helpful in teaching material in behavioral or psychomorphic domains, are faster and more effective in conveying messages than text media, and are able to clearly demonstrate simulations (Tegeh et al, 2019). Learning media can make students learn independently because they are able to explain real about the learning material.…”
Section: Resultsmentioning
confidence: 99%
“…Produk media pembelajaran lainnya yang dikembangkan pada konten e-learning ini adalah video pembelajaran. Hal ini sejalan penelitian yang dilakukan oleh (Tegeh et al, 2019) menyatakan bahwa yang video menarik dapat menarik perhatian siswa dalam belajar, sehingga dapat meningkatkan hasil belajar. Berdasarkan penilaian tersebut maka dapat disimpulkan bahwa, video pembelajaran yang telah dikembangkan layak digunakan untuk membantu siswa dalam belajar pada Mata Pelajaran Seni Budaya.…”
Section: Pembahasanunclassified